Analisis Penerapan Keselamatan Dan Kesehatan Kerja (K3) Pada PT. XYZ - Karawang - Ela Nuraliasari; Nandang Nandang; Zenita Apriani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
One way to prevent work accidents in the workplace is to establish a management system that can protect labor and work accidents and avoid large losses to the company. The implementation of occupational safety and health (K3) in an organization must be carried out jointly both by the leadership and by employees so that the possibility of accidents and occupational diseases can be avoided. The purpose of this research is to find out, analyze and explain how the implementation of occupational safety and health (K3) at PT. XYZ. The method used in the research is descriptive qualitative aimed at describing the application of occupational safety and health (OHS) carried out by PT. XYZ. Data collection was carried out by interview, observation and literature study. Data analysis was carried out descriptively qualitative by comparing the results of observations with the results of research on the implementation of occupational safety and health (OHS) with theories obtained from literature studies. The results showed that Occupational Safety and Health (OHS) has been implemented and implemented properly at PT. XYZ. This makes it possible to reduce occupational safety and health risks at PT. XYZ, as evidenced by a number of significant indicators that have been adopted in accordance with the requirements. All partners in the company must work together, including leaders, management, and employees, to create a safe and healthy working environment.